(untitled) (Research, Society and Development, 2021)
Objective. This study aims to assess the knowlegde of the women about the practice of crossfeeding. Methods. Observational, prospective and analytical study carried out in a Philanthropic Hospital and Maternity in Aracaju SE, from August to November 2021. The population used in the research consisted of mothers referred to rooming-in and specialized outpatient clinic of the Hospital and Maternity Santa Isabel, being applied a questionnaire by the researchers. Results. The prevalence of cross-breastfeeding was 49.16%, considering that 31.11% (n=42) of the mothers breastfed one or more children other than their child and 18.05% (n=24) had their child breastfed for one or more nursing mothers. 62.22% of them did not know what cross-breastfeeding was. 52, 59% were aged between 21 and 30 years. As for the race, most were configured as non-white. 16.30% lived in rural areas. Less than half, 40.60%, declared themselves to be married or in a stable relationship. 74.81%, lived with less than one salary at one minimum wage per month and also did not have a formal paid job, 87.41%. 65.19% of them received Bolsa Família aid. Only 5.19% had completed or incomplete higher education. When the variables were compared, two P-values were noted with significance levels, p=0.002 and p=0.031, corresponding to whether mothers knew the risk of cross-breastfeeding or whether they had been breastfed by a woman other than the mother, respectively. Conclusion. Despite being prohibited in Brazil, crossfeeding is still recurrent, in high percentages and there is a lack of information on the subject.